Effect of GDF-9 and bFGF in combination on caprine granulosa cell growth parameters in vitro - PAVANA SHREE, U S; NANDI, S; KUMAR, V GIRISH; GUPTA, P S P; MURTHY, V CHANDRASEKHAR (The Indian Journal of Animal Sciences, 2014)
The present study was undertaken to examine the effect of GDF-9 and bFGF on in vitro growth of granulosa cells in goats. Granulosa cell number increment and monolayer formation score were significantly higher in media containing GDF-9 and bFGF at 20 ng/ml. No significant difference was observed in viability, MTT oxidation and ability of granulosa cell monolayer to support oocyte maturation between control and treatment groups. In conclusions, GDF-9 and FGF at 20 ng/ml improved granulosa cell functions and oocyte maturation indicating its influence on the mechanism of oocyte growth.